Archaic words in Tuvan heroic legends - Ondar, Mengi V. (The New Research of Tuva, 2020)
The article analyzes outdated words in the texts of Tuvan heroic tales. Epic tales are usually believed to be very old, and their language archaic. But despite its antiquity, the language of heroic tales is periodically updated and developed in accordance with changing processes in the language of the ethnic group preserving these tales. The sources of the study 38 Tuvan heroic tales originally published in different collections. They have recently been organized into a separate database within the Electronic corpus of the Tuvan language (http://www.tuvancorpus.ru/). The collected material shows that outdated words in Tuvan heroic tales are divided into the following thematic groups: words referring to the character’s title or status; names of military weapons and attributes of the hero; words referring to household items; and names of human body parts. Our analysis revealed 13 archaisms and 9 historicisms, of which 10 are Mongolian borrowings, and the rest are of Turkic origin. Some obsolete words from these groups are now returning to active vocabulary of the Tuvan language, having acquired a new meaning.